Ocular surface repair material with slow release effect and preparation method thereof
By preparing eye surface repair materials with sustained release, using the combination of engineered HC-HA/PTX3 composite and contact lens materials, the problems of surgical time and complications in the prior art are solved, and the therapeutic effect of stably releasing biological active ingredients is achieved.
Patent Information
- Application Number
- CN202510035094.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-04-11
AI Technical Summary
In the treatment of ocular surface and corneal injury or absence, the operation takes a long time, sutures irritate the ocular surface, and there are complications, such as the formation of corneal neovascularization, affecting visual function.
The preparation method of the eye surface repair material with a sustained release effect includes constructing an engineered HC-HA/PTX3 composite, preparing nanoparticles containing the composite, and combining it with the contact lens material, forming a nanoparticle suspension through emulsification and ionization, and finally preparing the eye surface repair material.
This material can stably release biologically active ingredients for a long time, with good treatment effect, and the contact lens material is non-toxic and will not irritate the eyes. It is suitable for the treatment of a variety of ocular surface diseases.
Smart Images

Figure CN119792554A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of medical devices, and specifically relates to an ocular surface repair material with sustained-release effect and a preparation method thereof. Background Art
[0002] Various ocular surface diseases such as chemical injuries, thermal burns, and keratitis can cause damage or loss of the cornea and conjunctiva, and are often accompanied by the formation of corneal neovascularization, which in turn affects visual function. Currently, the commonly used treatment for ocular surface and corneal damage or loss is to cover the ocular surface with an ocular dressing. The dressing usually uses a multi-needle double continuous or interrupted suture method, which makes the operation relatively time-consuming, "sutures" irritate the ocular surface, and "sutures" cause complications and other inherent defects.
[0003] Invention patent CN104619352B discloses a composition containing HC-HA / PTX3 complex and a method of using the same, and provides a method for producing natural and reconstructed hyaluronan (HA) complexes, a composition containing the complex, and a treatment method using the complex. However, it does not disclose how to better use the HC-HA / PTX3 complex for ocular surface repair. Summary of the invention
[0004] In view of the deficiencies in the prior art, the present invention provides an ocular surface repair material with sustained-release effect and a preparation method thereof.
[0005] The technical solution of the present invention is:
[0006] A method for preparing an ocular surface repair material with a sustained-release effect comprises the following steps:
[0007] S1. constructing an engineered HC-HA / PTX3 complex: dissolving the HC-HA / PTX3 complex and adding it to a cross-linking agent, and coupling it with an antibody to obtain an engineered HC-HA / PTX3 complex;
[0008] S2. Preparing nanoparticles containing the engineered HC-HA / PTX3 complex: adding the engineered HC-HA / PTX3 complex prepared in step S1 to the sustained-release material solution, stirring evenly, emulsifying, ion gelling to form a nanoparticle suspension, and then centrifuging, washing, and freeze-drying to obtain nanoparticles containing the engineered HC-HA / PTX3 complex;
[0009] S3. Preparing ocular surface repair material: mixing the nanoparticles prepared in step S2 with the contact lens material solution, pouring into a mold, cross-linking and curing, and demolding to obtain the ocular surface repair material.
[0010] Furthermore, step S1 is specifically as follows:
[0011] S101. The HC-HA / PTX3 complex is dissolved in MES buffer to obtain an HC-HA / PTX3 complex solution with a concentration of 1-5 mg / ml, and a cross-linking agent solution is added thereto for reaction for 15-30 min to obtain an activated HC-HA / PTX3 complex, wherein the volume ratio of the cross-linking agent solution to the HC-HA / PTX3 complex solution is (1-2):(1-2);
[0012] S102. Prepare an antibody solution with a concentration of 1-10 mg / ml, add the activated HC-HA / PTX3 complex obtained in S101 to the antibody solution, and react for 2-4 hours. The volume ratio of the antibody solution to the activated HC-HA / PTX3 complex is (1-2):(1-2);
[0013] S103. Add glycine or ethanolamine to terminate the reaction, dialyze, centrifuge and concentrate to obtain the engineered HC-HA / PTX3 complex.
[0014] Furthermore, the antibody solution in S102 is an anti-TNF-α antibody solution.
[0015] Furthermore, the preparation method of the cross-linking agent solution in S101 is to dissolve EDC and NHS in MES buffer, the mass ratio of EDC to NHS is (10-13):(10-13), and the concentration of the cross-linking agent solution is 10 mg / ml-100 mg / ml.
[0016] Furthermore, the specific steps of step S2 are:
[0017] S201. Preparing a sustained-release material solution: dissolving the sustained-release material in a dilute acetic acid solution, stirring to obtain a sustained-release material solution, wherein the concentration of the sustained-release material solution is 1-2% w / v;
[0018] S202. Emulsification: adding the engineered HC-HA / PTX3 complex prepared in S1 to the sustained-release material solution to obtain an intermediate solution A, and adding the intermediate solution A dropwise to the aqueous phase containing the emulsifier, and forming an emulsion by ultrasound;
[0019] S203. Ionic gelation: The emulsion prepared in S202 is added dropwise to an aqueous phase containing calcium ions, stirred to form ionic gel nanoparticles, and then centrifuged, washed, and freeze-dried to obtain nanoparticles containing the engineered HC-HA / PTX3 complex.
[0020] Furthermore, the concentration of the dilute acetic acid solution in step S201 is 0.5%-1%.
[0021] Furthermore, in step S202, the volume ratio of the engineered HC-HA / PTX3 complex to the sustained-release material solution is 1:(2-5).
[0022] Furthermore, the contact lens material solution in step S3 is a mixture of monomers, crosslinking agents, and photoinitiators, wherein the monomers are one or more of HEMA, MMA, and NVP, the crosslinking agent is EGDMA, and the photoinitiator is Irgacure 2959, wherein the mass percentage of the crosslinking agent is 0.5%-5%, the mass percentage of the photoinitiator is 0.1%-2%, and the remainder is the monomers.
[0023] Furthermore, in step S3, the mass ratio of the nanoparticles to the contact lens material solution is (1-3):100.
[0024] The ocular surface repair material is prepared according to the above preparation method.
[0025] Compared with the prior art, the present invention has at least the following advantages:
[0026] 1. The present invention relates to a method for preparing an ocular surface repair material with a sustained-release effect, the preparation process is simple, easy to promote, highly practical, and has good economic benefits.
[0027] 2. The ocular surface repair material with sustained release effect prepared by the method of the present invention contains sustained release material and nanoparticles containing engineered HC-HA / PTX3 complex, wherein the HC-HA / PTX3 complex contains biologically active ingredients, thereby ensuring that the ocular surface repair material can stably release effective biologically active ingredients over a long period of time and has a good therapeutic effect; the ocular surface repair material also contains contact lens material with good biocompatibility, which is non-toxic and will not irritate the eyes.
[0028] 3. The ocular surface repair material with sustained release prepared by the method of the present invention has broad application prospects and can be used to treat a variety of ocular surface diseases, such as ocular surface defects, dry eyes, keratitis, postoperative repair and other diseases. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the specific embodiments of the present invention, the drawings required for use in the specific embodiments or the description of the prior art will be briefly introduced below.
[0030] Figure 1 a is a state diagram of the ocular surface repair material prepared in Example 1 of the present invention after being buckled on the right eye of an experimental rabbit for 14 days; b is a diagram of the area of the corneal defect fluorescence positive area;
[0031] Figure 2 a is a state diagram of the ocular surface repair material prepared in Example 2 of the present invention after being buckled on the right eye of an experimental rabbit for 14 days; b is a diagram of the area of the corneal defect fluorescence positive area;
[0032] Figure 3a is a state diagram of the ocular surface repair material prepared in comparative example 1 of the present invention after being buckled on the right eye of the experimental rabbit for 14 days; b is a diagram of the area of the corneal defect fluorescence positive area;
[0033] Figure 4 a is the status of the eyes in the control group 14 days after surgery; b is the area of the corneal defect fluorescence-positive area. DETAILED DESCRIPTION
[0034] In order to make the purpose, technical solution and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments, but it should not be understood as limiting the scope of protection of the present invention. Any equivalent changes in form made based on the concept of the present invention should be regarded as the scope of the present invention.
[0035] The present invention provides a general and / or specific description of the materials and test methods used in the experiment. The test methods or test methods involved are all conventional methods unless otherwise specified; the reagents or instruments used are all conventional products available on the market, prepared or used in a conventional manner, unless the manufacturer is specified.
[0036] Sources
[0037] Hydroxyethyl methacrylate (HEMA): purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., product number: H103044;
[0038] Methyl methacrylate (MMA): purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., catalog number: M109629;
[0039] N-vinylpyrrolidone (NVP): purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., catalog number: V106155;
[0040] Ethylene glycol dimethacrylate (EGDMA): purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., catalog number: E684416;
[0041] 2-Hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone (Irgacure 2959): purchased from Sigma-Aldrich, catalog number: 410896;
[0042] Anti-TNF-α antibody: purchased from AntibodySystem, catalog number: MHB9440;
[0043] HC-HA / PTX3 complex: prepared by referring to the method in paragraphs 0528 to 0538 of Example 1 in invention patent CN104619352B.
[0044] Example 1 Example 1 is a method for preparing an ocular surface repair material with sustained release effect
[0045] 1. Prepare contact lens material solution
[0046] The contact lens material solution is composed of monomers, crosslinking agents and photoinitiators, wherein the monomers are composed of HEMA (hydroxyethyl methacrylate), MMA (methyl methacrylate) and NVP (N-vinyl pyrrolidone), the crosslinking agent is EGDMA (ethylene glycol dimethacrylate), and the photoinitiator is Irgacure 2959 (2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone). 60 mg of HEMA, 7 mg of MMA, 30 mg of NVP, 2 mg of EGDMA and 1 mg of Irgacure 2959 are weighed and mixed uniformly to obtain a contact lens material solution.
[0047] 2 Construction of engineered HC-HA / PTX3 complex
[0048] 2.1 Activation of crosslinker
[0049] Prepare the crosslinker solution: dissolve 10 mg of EDC and 10 mg of NHS in 1 mL of MES buffer to prepare the crosslinker solution;
[0050] Preparation of HC-HA / PTX3 complex solution: 1 mg of HC-HA / PTX3 complex was dissolved in 1 mL of MES buffer and stirred to obtain HC-HA / PTX3 complex solution;
[0051] 1 mL of the cross-linker solution was added to the HC-HA / PTX3 complex solution and reacted at room temperature for 15 min to obtain an activated cross-linker;
[0052] 2.2 Coupling specific antibodies
[0053] Prepare 2 mL of PBS buffer containing anti-TNF-α antibody at a concentration of 1 mg / mL, add it to 2 mL of the activated cross-linker prepared in step 2.1, stir evenly, and react at 4°C for 2 hours, avoiding light and vigorous shaking;
[0054] 2.3 Reaction termination and purification
[0055] 6 mg of glycine was added to the reaction solution of 2.2 to terminate the reaction, and unreacted cross-linking agent and small molecule impurities were removed by dialysis. The engineered HC-HA / PTX3 complex was obtained by centrifugal filtration through an Amicon Ultra-15 centrifugal filter.
[0056] 3 Preparation of Nanoparticles Containing Engineered HC-HA / PTX3 Complexes
[0057] 3.1 Preparation of sustained-release material solution
[0058] Dissolve 1 g of chitosan in 100 mL of 0.5% dilute acetic acid solution and stir well to form a 1% w / v chitosan solution;
[0059] Add 4 mL of the engineered HC-HA / PTX3 complex prepared in step 2 to 20 mL of the chitosan solution and stir evenly to form a chitosan-engineered HC-HA / PTX3 complex solution;
[0060] 3.2 Emulsification
[0061] 4 mL of the chitosan-engineered HC-HA / PTX3 complex solution was slowly added dropwise to 20 mL of an aqueous phase containing 2% (v / v) Tween 80 to form an emulsion under ultrasonic conditions;
[0062] 3.3 Ion gelation
[0063] Take 20 mL of the above emulsion and slowly add it dropwise into 20 mL of 1% w / v CaCl2 solution, and stir at a low speed of 500 rpm for 1 hour to form gel nanoparticles;
[0064] 3.4 Nanoparticle collection and cleaning
[0065] The nanoparticle suspension prepared in 3.3 was collected by high-speed centrifugation at a speed of 12000 rpm for 15 min, and the precipitate was washed several times with sterile PBS to remove the unencapsulated complex and excess calcium ions;
[0066] 3.5 Drying and storage of nanoparticles
[0067] The washed nanoparticles are freeze-dried to obtain dry nanoparticle powder containing the engineered HC-HA / PTX3 complex, which is stored under low-temperature drying conditions for future use.
[0068] 4. Preparation of active ocular surface repair materials
[0069] 1 mg of the prepared nanoparticle powder containing the engineered HC-HA / PTX3 complex was added to 100 mg of the contact lens material solution and mixed thoroughly, then loaded into a contact lens mold, cross-linked and cured, and after demolding, an ocular surface repair material with a sustained release effect was obtained.
[0070] Example 2 This example is a method for preparing an ocular surface repair material with sustained release effect
[0071] 1. Prepare contact lens material solution
[0072] The contact lens material solution is composed of monomers, a crosslinking agent and a photoinitiator, wherein the monomers are composed of HEMA (hydroxyethyl methacrylate), MMA (methyl methacrylate) and NVP (N-vinyl pyrrolidone), the crosslinking agent is EGDMA (ethylene glycol dimethacrylate), and the photoinitiator is Irgacure 2959 (2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone). 80 mg of HEMA, 5 mg of MMA, 10 mg of NVP, 3 mg of EGDMA and 2 mg of Irgacure 2959 are weighed and mixed uniformly to obtain a contact lens material solution.
[0073] 2 Construction of engineered HC-HA / PTX3 complex
[0074] 2.1 Activation of crosslinker
[0075] Prepare crosslinker solution: dissolve 13 mg of EDC and 13 mg of NHS in 1 mL of MES buffer to prepare crosslinker solution;
[0076] Preparation of HC-HA / PTX3 complex solution: 5 mg of HC-HA / PTX3 complex was dissolved in 1 mL of MES buffer and stirred to obtain HC-HA / PTX3 complex solution;
[0077] 1 mL of the cross-linker solution was added to the HC-HA / PTX3 complex solution and reacted at room temperature for 30 min to obtain an activated cross-linker;
[0078] 2.2 Coupling specific antibodies
[0079] Prepare 2 mL of PBS buffer containing anti-TNF-α antibody at a concentration of 10 mg / mL, add it to 2 mL of the activated cross-linker prepared in step 2.1, stir evenly, and react at 4°C for 4 hours, avoiding light and vigorous shaking;
[0080] 2.3 Reaction termination and purification
[0081] 6 mg of ethanolamine was added to the reaction solution of 2.2 to terminate the reaction, and the unreacted cross-linking agent and small molecule impurities were removed by gel filtration (Sephadex G-25 column). The engineered HC-HA / PTX3 complex was obtained by centrifugal filtration through an Amicon Ultra-15 centrifugal filter.
[0082] 3 Preparation of Nanoparticles Containing Engineered HC-HA / PTX3 Complexes
[0083] 3.1 Preparation of sustained-release material solution
[0084] Dissolve 2 g of PLGA (poly(lactic-co-glycolic acid)) in 100 mL of 0.5% dilute acetic acid solution and stir well to form a 2% w / v PLGA solution;
[0085] Add 4 mL of the engineered HC-HA / PTX3 complex prepared in step 2 to 12 mL of the PLGA solution and stir evenly to form a PLGA-engineered HC-HA / PTX3 complex solution;
[0086] 3.2 Emulsification
[0087] 4 mL of the above PLGA-engineered HC-HA / PTX3 complex solution was slowly added dropwise to 20 mL of an aqueous phase containing 2% (v / v) Tween 80 to form an emulsion under high-speed stirring (12000 rpm);
[0088] 3.3 Ion gelation
[0089] 20 mL of the above emulsion was slowly added dropwise to 20 mL of 1% w / v CaCl2 solution and stirred at 500 rpm for 2 hours to form gel nanoparticles;
[0090] 3.4 Nanoparticle collection and cleaning
[0091] The nanoparticle suspension prepared in 3.3 was collected by high-speed centrifugation at a speed of 12000 rpm for 15 min, and the precipitate was washed several times with sterile PBS to remove the unencapsulated complex and excess calcium ions;
[0092] 3.5 Drying and storage of nanoparticles
[0093] The washed nanoparticles are dried in a vacuum dryer to obtain dry nanoparticle powder containing the engineered HC-HA / PTX3 complex, which is stored under low-temperature drying conditions for future use.
[0094] 4. Preparation of active ocular surface repair materials
[0095] 3 mg of the prepared nanoparticle powder containing the engineered HC-HA / PTX3 complex was added to 100 mg of the contact lens material solution and mixed thoroughly, then loaded into a contact lens mold, cross-linked and cured, and after demolding, an ocular surface repair material with a sustained release effect was obtained.
[0096] Comparative Example 1
[0097] This comparative example is substantially the same as Example 1, except that the engineered HC-HA / PTX3 complex is not added.
[0098] Application Examples
[0099] In order to verify the clinical application effect of the ocular surface repair material with sustained release effect prepared by the present invention, this application example uses an animal model with corneal epithelial and stromal layer damage, simulates the use of the ocular surface repair material according to clinical requirements, and examines the product performance of the ocular surface repair material with sustained release effect provided by the present invention and the effectiveness of repairing corneal wounds.
[0100] S1. Establishing animal models
[0101] Eight New Zealand rabbits (2±0.5kg) were anesthetized with intravenous injection of sodium pentobarbital, and then placed in lateral recumbency. The head position was adjusted so that the ocular surface was facing upwards, and the hair around the eyes was shaved. The periocular area and ocular surface were rinsed and disinfected alternately with diluted iodine disinfectant and normal saline. Subsequently, local anesthetic was applied to the ocular surface, and the ocular surface anesthetic was applied to the operated eye three times before the operation. An eyelid speculum was used to expose the ocular surface, and normal saline should be added at appropriate times during the operation to reduce the drying of the cornea due to long-term exposure during the operation. A corneal trephine with a diameter of 6 mm and adjustable cutting depth was used, and the cutting area was 25 to 40 mm. 2 The lamellar cornea was removed along the indentation using a corneal tunnel knife to prepare an animal model of corneal epithelial and stromal layer damage.
[0102] The successfully established animal models were randomly divided into 4 groups, including experimental group 1: the ocular surface repair material with sustained release prepared in Example 1 was buckled on the right eye of the rabbits in the experimental group; experimental group 2: the ocular surface repair material with sustained release prepared in Example 2 was buckled on the right eye of the rabbits in the experimental group; control group 1: the ocular surface repair material prepared in comparative example 1 was buckled on the right eye of the rabbits in the experimental group; control group 2: no treatment was done on the operated eye.
[0103] S2. Surgical method
[0104] All surgical operations were performed using sterile surgical instruments and in strict accordance with clinical surgical requirements.
[0105] The animal model (2±0.5kg) was anesthetized by intravenous injection of sodium pentobarbital, and the front and rear limbs were fixed with ropes. The whole body of the experimental rabbit was wrapped with a surgical towel, and the hair around the right eye of the rabbit was removed with an electric shaver. It was disinfected with iodine to minimize the impact on the surgical process and subsequent corneal repair. The surgical site was the wound area of the corneal epithelial and stroma layer injury model.
[0106] S3. Postoperative evaluation
[0107] The mental state and activity of the experimental rabbits were observed every day, and the corneal repair was observed. The evaluation method was to observe the corneal turbidity and corneal neovascularization of each group of rabbits 14 days after surgery, and comprehensively evaluate the effectiveness of the ocular surface repair material with sustained release provided by the present invention on ocular surface repair.
[0108] S4. Results
[0109] Table 1 Measurement and evaluation of corneal defect area in each group
[0110]
[0111] Note: The fluorescence positive area is expressed as the mean ± SD of each group.
[0112] like Figure 1 a. Figure 2 As shown in a, the experimental rabbits in experimental groups 1 to 2 had all completed epithelialization 14 days after surgery. The corneas of the rabbits in experimental groups 1 to 2 were clear and transparent, no new blood vessels grew into the wound area, and the corneal defects were completely repaired (see Table 1, Figure 1 b. Figure 2 b) If Figure 3 As shown in a, a small amount of new blood vessels can be seen growing into the wound area of the cornea of the rabbit in the control group 1, and there is a slight scar on the cornea (at the pupil) and a small corneal defect area (see Table 1, Figure 3 b) If Figure 4 As shown in a, a large number of new blood vessels grew into the wound area of the cornea (pupil) of the rabbit in the control group 2, and the conjunctiva was severely congested and edematous, with severe scars. The corneal defect area was large (see Table 1, Figure 4 b).
[0113] It can be seen that the ocular surface repair material with sustained release effect provided by the present invention can play an anti-scarring and neovascularization inhibitory role in clinical use. At the same time, the ocular surface repair material with sustained release effect provided by the present invention is convenient for clinical use and saves surgical time.
[0114] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. These modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention, and they should all be included in the scope of the claims and specification of the present invention.
Claims
1. A method for preparing an ocular surface repair material with sustained release effect, characterized in that: The following steps are involved: S1. constructing an engineered HC-HA / PTX3 complex: dissolving the HC-HA / PTX3 complex and adding it to a cross-linking agent, and coupling it with an antibody to obtain an engineered HC-HA / PTX3 complex; S2. Preparing nanoparticles containing the engineered HC-HA / PTX3 complex: adding the engineered HC-HA / PTX3 complex prepared in step S1 to the sustained-release material solution, stirring evenly, emulsifying, ion gelling to form a nanoparticle suspension, and then centrifuging, washing, and freeze-drying to obtain nanoparticles containing the engineered HC-HA / PTX3 complex; S3. Preparing an ocular surface repair material: mixing the nanoparticles prepared in step S2 with the contact lens material solution, pouring the mixture into a mold, cross-linking and curing the mixture, and demolding the mixture to obtain an ocular surface repair material.
2. The preparation method according to claim 1, characterized in that: Step S1 is specifically as follows: S101. The HC-HA / PTX3 complex is dissolved in MES buffer to obtain an HC-HA / PTX3 complex solution with a concentration of 1-5 mg / ml, and a cross-linking agent solution is added thereto for reaction for 15-30 min to obtain an activated HC-HA / PTX3 complex, wherein the volume ratio of the cross-linking agent solution to the HC-HA / PTX3 complex solution is (1-2):(1-2); S102. Prepare an antibody solution with a concentration of 1-10 mg / ml, add the activated HC-HA / PTX3 complex obtained in S101 to the antibody solution, and react for 2-4 hours. The volume ratio of the antibody solution to the activated HC-HA / PTX3 complex is (1-2):(1-2); S103. Add glycine or ethanolamine to terminate the reaction, dialyze, centrifuge and concentrate to obtain the engineered HC-HA / PTX3 complex.
3. The preparation method according to claim 2, characterized in that: The antibody solution in S102 is an anti-TNF-α antibody solution.
4. The preparation method according to claim 3, characterized in that: The preparation method of the cross-linking agent solution in S101 is to dissolve EDC and NHS in MES buffer, the mass ratio of EDC to NHS is (10-13):(10-13), and the concentration of the cross-linking agent solution is 10 mg / ml-100 mg / ml.
5. The preparation method according to claim 1, characterized in that: The specific steps of step S2 are: S201. Preparing a sustained-release material solution: dissolving the sustained-release material in a dilute acetic acid solution, stirring to obtain a sustained-release material solution, wherein the concentration of the sustained-release material solution is 1-2% w / v; S202. Emulsification: adding the engineered HC-HA / PTX3 complex prepared in S1 to the sustained-release material solution to obtain an intermediate solution A, and adding the intermediate solution A dropwise to the aqueous phase containing the emulsifier, and forming an emulsion by ultrasound; S203. Ionic gelation: The emulsion prepared in S202 is added dropwise to an aqueous phase containing calcium ions, stirred to form ionic gel nanoparticles, and then centrifuged, washed, and freeze-dried to obtain nanoparticles containing the engineered HC-HA / PTX3 complex.
6. The preparation method according to claim 5, characterized in that: The concentration of the dilute acetic acid solution in step S201 is 0.5%-1%.
7. The preparation method according to claim 6, characterized in that: In step S202, the volume ratio of the engineered HC-HA / PTX3 complex to the sustained-release material solution is 1:(2-5).
8. The preparation method according to claim 1, characterized in that: The contact lens material solution in step S3 is a mixture of monomers, crosslinking agents, and photoinitiators, wherein the monomers are one or more of HEMA, MMA, and NVP, the crosslinking agent is EGDMA, and the photoinitiator is Irgacure 2959, wherein the mass percentage of the crosslinking agent is 0.5%-5%, the mass percentage of the photoinitiator is 0.1%-2%, and the remainder is the monomers.
9. The preparation method according to claim 1, characterized in that: The mass ratio of the nanoparticles to the contact lens material solution in step S3 is (1-3):
100.
10. An ocular surface repair material prepared according to the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Compositions containing HC-HA / PTX3 complex and their methods of use
CN104619352B